Przejawy naruszeń praw i interesów klientów biur podróży i gości hotelowych w Polsce - Jedlińska, Maja (The Signs of Violating Laws and Interests of Travel Offices' Clients and Hotel Guests in Poland, 2005)
Poland - as the member of the European Union - has to meet the requirements resulting from legislative regulations in force in many areas, also in tourism. The hereby study presents the European Union directives, referring to tourism movement, which have been reflected in Polish legislation. In order to verify their practical application, there has been conducted empirical research, in a few provinces (complaints by travel offices' clients) and in hotels. The occurring problems, which are outside the sphere of legislative regulations, have been touched upon. Directions for further modifications of Polish legislation have been presented and the suggestions for taking advantage of German experiences have been given, where tourist's rights have been included in the Civil Code.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 273-284